2016
DOI: 10.4103/0971-9784.191550
|View full text |Cite
|
Sign up to set email alerts
|

Early enteral nutrition therapy in congenital cardiac repair postoperatively: A randomized, controlled pilot study

Abstract: Background and Objectives:Adequate nutritional supplementation in infants with cardiac malformations after surgical repair is a challenge. Critically ill infants in the early postoperative period are in a catabolic stress. The mismatch between estimated energy requirement (EER) and the intake in the postoperative period is multifactorial, predisposing them to complications such as immune deficiency, more infection, and growth failure. This study aimed to assess the feasibility and efficacy of enriched breast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…Although previous studies have demonstrated that infants tolerate higher amounts of macronutrients after surgery well, there is still insecurity in feeding these patients because of their clinical severity. This study may contribute to demonstrating that patients tolerate well EE formula after surgery, and the benefits may be seen early after intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have demonstrated that infants tolerate higher amounts of macronutrients after surgery well, there is still insecurity in feeding these patients because of their clinical severity. This study may contribute to demonstrating that patients tolerate well EE formula after surgery, and the benefits may be seen early after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned study has also observed a reduction in HLOS, as was observed in this study. Similarly, another randomized study evaluated the use of human milk fortifier and described a trend in reduction in length of MV, ICULOS, and HLOS. A case control study evaluated the implementation of a feeding protocol for the initiation and advancement of enteral feeding in children with CHD and observed a reduction in HLOS after the implementation.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that postoperative feeding via an enteric tube is effective in its ability to provide adequate nutrition for recovery in patients with complex CHD, and Newcombe et al have shown that using a standard postoperative nutritional pathway has led to improved outcomes. [23][24][25] Limitations This study is limited by its retrospective design; therefore, we can only identify associations with our outcome and are unable to establish a cause and effect. Our goal was to understand possible risk factors for feeding tube use at time of discharge to allow for early institution of feeding tubes in high-risk populations to reduce hospital length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure (CHF) is a serious and growing public health problem worldwide, being the final common pathway of most heart diseases [ 1 , 2 ]. Although the scientific and technological advances and the better socioeconomic conditions have allowed the increase of the longevity of the general population and of the cardiac patients, there has been an increase in the incidence of CHF in the world [ 2 - 4 ]. Approximately 23 million people are carriers of this disease and two million new cases are diagnosed each year.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 23 million people are carriers of this disease and two million new cases are diagnosed each year. CHF is an important public health issue due to its high prevalence, severity of clinical manifestations and reserved prognosis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%